On the convergence of Dirichlet series in boundary points of convergence domain - Kabaila, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Кабайла. Заметка о сходимости ряда Дирихле на границе области сходимостиV. Kabaila. Apie Dirichlė eilutės konvergavimą konvergencijos srities kontūro taškuose